Evaluation of the Drainage Channel Capacity of Air Ukah in Ngabang - Barage, Lourdes Meirista; Gunarto, Danang; Soeryamassoeka, S. B. (Jurnal Teknik Sipil, 2024)
Flooding in Ngabang, Landak Regency, Kalimantan Barat often results from high rainfall, urban expansion, and limited drainage. This study analyzes the Air Ukah drainage system, including primary, secondary, and tertiary channels, to assess current capacities against projected rainfall intensities. Hydraulic and hydrological analyses were performed using primary field data and validated rainfall records from 1999-2020. Findings reveal that the existing drainage, with the primary channel"™s 5.20 m ³/s capacity, the secondary channel at 0.36 m ³/s, and tertiary channels at 0.82 m ³/s, cannot accommodate maximum discharge, particularly for a 100-year return period rainfall of 114.27 mm/hour. To address this, channels were expanded: the primary channel was widened to 6.5 m and deepened to 3.5 m, increasing its capacity to 11.83 m ³/s. The secondary and tertiary channels were similarly upgraded, now accommodating 2.40 m ³/s and a cumulative 34.07 m ³/s. These modifications significantly enhance drainage capacity, preparing Ngabang to handle intense rain events and mitigating flood risks, particularly in urban areas. This upgraded system now meets the need for resilience against extreme rainfall, ensuring improved water management and community safety.